2020
DOI: 10.2340/00015555-3661
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Seborrhoeic Dermatitis Flares: Case-control and Case-crossover Study

Abstract: Patients with flares of seborrhoeic dermatitis were compared with control outpatients seen during the same time-period in a case-control study, and with themselves while in remission in a case-crossover study. All patients consulted the same office-based dermatologist. During the study period, 189 cases and 189 controls were included in the case-control study, and 81 cases in the case-crossover study. Multivariate analysis was performed. Case-control study results were the following: past history of tobacco co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…34 Male gender, age, obesity, skin type, education, HT, depression, stress, and diet are risk factors that facilitate the formation of SD. 35 Although SD is a dermatosis mostly seen in men, it was more common in women in this study, similar to that in Iraq. 28 Regardless of age, there is an increase in the occurrence of MetS as a result of hormonal changes during menopause.…”
Section: Patients Without Mets Psupporting
confidence: 75%
See 1 more Smart Citation
“…34 Male gender, age, obesity, skin type, education, HT, depression, stress, and diet are risk factors that facilitate the formation of SD. 35 Although SD is a dermatosis mostly seen in men, it was more common in women in this study, similar to that in Iraq. 28 Regardless of age, there is an increase in the occurrence of MetS as a result of hormonal changes during menopause.…”
Section: Patients Without Mets Psupporting
confidence: 75%
“…Lancor et al detected the most involvement in the nasolabial, eyebrow, and scalp in SD patients aged 30–54 years 35 . In our study, there was scalp involvement in 72.2% ( n = 39) of the patients in general.…”
Section: Discussionsupporting
confidence: 54%
“…Koo and Lee, who classified psychodermatological diseases, included seborrheic dermatitis in the category of psychophysiological disorders referring to the precipitation or exacerbation of a skin disease by psychological stress [25]. Many studies have shown the negative effect of stress on the severity of seborrheic dermatitis and frequency of disease attacks [12,[26][27][28][29]. It is known that the quality of life is significantly affected in this chronic disease with recurrent attacks (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies found significant associations between regular alcohol use and an increased prevalence of SD [17,18,19,20] Further, increased alcohol consumption is associated with a greater risk of SD flares (OR = 5.4, P = .08) [20]. Sharma et al evaluated quantity of alcohol consumed in a week, duration of alcohol intake, and SD duration in 196 males, who reported drinking ≥200 mL of pure alcohol weekly, that were referred for a dermatologic consult [17].…”
Section: Alcoholmentioning
confidence: 99%
“…Some studies demonstrate no relationship between SD and BMI [10, 19,20]; however, a casecontrol study by Akbas et al (n = 101) compared SD patients with age and sex matched controls and found that SD was associated with higher BMI when compared to controls (P = .002) [22]. Erdogan et al (n = 103) also evaluated the relationship between BMI, subjective SD severity, and SDASI score in a case control study with SD patients and age, sex, and BMI matched controls [23].…”
Section: Obesitymentioning
confidence: 99%